2020
DOI: 10.1155/2020/9648056
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV‐1 Protease by Carpobrotus edulis (L.)

Abstract: Carpobrotus edulis (L.) is a plant commonly found in the Eastern Cape Province of South Africa and is used for the general treatment of infections relating to the human immunodeficiency virus (HIV). HIV-1 protease plays an important role during HIV replication and maturation to its infectious form, and therefore inhibition of the enzyme is one of the main focus areas in drug development. The inhibitory effect of a water extract of C. edulis leaves against HIV-1 protease activity was determined using the SensoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Developing these replication assays to represent all possible target sites in the HIV-1 genome will allow for rapid and unbiased screening of natural microbial products against various targets and save costs and time for hit identification [64,65]. Furthermore, full replication assays will also provide insight into protein-protein interactions, and thus increase the early small molecular compound screening capacity for future viral inhibitors [61,[66][67][68][69][70][71][72][73][74][75][76]. The fungal kingdom presents a great source of small therapeutic compounds with…”
Section: Advances In Antiviral Screening Assaysmentioning
confidence: 99%
“…Developing these replication assays to represent all possible target sites in the HIV-1 genome will allow for rapid and unbiased screening of natural microbial products against various targets and save costs and time for hit identification [64,65]. Furthermore, full replication assays will also provide insight into protein-protein interactions, and thus increase the early small molecular compound screening capacity for future viral inhibitors [61,[66][67][68][69][70][71][72][73][74][75][76]. The fungal kingdom presents a great source of small therapeutic compounds with…”
Section: Advances In Antiviral Screening Assaysmentioning
confidence: 99%
“…These phytochemicals compounds present in the leaf and callus extracts are responsible for many biological activities (34).The presence of these phytochemicals strengthens the traditional use of the plant A. Serratus have medicinal value. The presence of alkaloids, saponins and tannins in plants play very important role in pharmaceutical field as reported (35). These compounds have various antibiotic properties and they are used in treating diseases caused by common pathogenic strains.…”
Section: Preliminary Phytochemical Screeningmentioning
confidence: 99%
“…In Africa, this species has been used in the folk treatment of human immunodeficiency virus infections, dysentery, skin wounds, throat infections, or digestive problems, among others [ 22 , 23 ]. Several studies have reported the antioxidant, antiproliferative, antimicrobial and antiviral activities of this plant [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%